2012
DOI: 10.1186/1479-5876-10-42
|View full text |Cite
|
Sign up to set email alerts
|

De novo sequencing of circulating miRNAs identifies novel markers predicting clinical outcome of locally advanced breast cancer

Abstract: BackgroundMicroRNAs (miRNAs) have been recently detected in the circulation of cancer patients, where they are associated with clinical parameters. Discovery profiling of circulating small RNAs has not been reported in breast cancer (BC), and was carried out in this study to identify blood-based small RNA markers of BC clinical outcome.MethodsThe pre-treatment sera of 42 stage II-III locally advanced and inflammatory BC patients who received neoadjuvant chemotherapy (NCT) followed by surgical tumor resection w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
179
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 219 publications
(184 citation statements)
references
References 36 publications
(44 reference statements)
4
179
1
Order By: Relevance
“…As an example, recent studies have identified specific microRNAs that are upregulated in the blood within hours after a heart attack and are currently investigating the use of these microRNAs as potential biomarkers for myocardial infarction (Salic and De Windt, 2012). microRNAs are widely used in several types of cancer, with one study identifying microRNAs that correlate with the clinical outcome of breast cancer patients (Wu et al, 2012). Currently, microRNAs are undergoing evaluation for possible clinical use as biomarkers for neurological diseases (de Planell-Saguer and Rodicio, 2011).…”
Section: Future Research Directionsmentioning
confidence: 99%
“…As an example, recent studies have identified specific microRNAs that are upregulated in the blood within hours after a heart attack and are currently investigating the use of these microRNAs as potential biomarkers for myocardial infarction (Salic and De Windt, 2012). microRNAs are widely used in several types of cancer, with one study identifying microRNAs that correlate with the clinical outcome of breast cancer patients (Wu et al, 2012). Currently, microRNAs are undergoing evaluation for possible clinical use as biomarkers for neurological diseases (de Planell-Saguer and Rodicio, 2011).…”
Section: Future Research Directionsmentioning
confidence: 99%
“…We have previously profiled small RNAs in the sera of 42 stage II-III BC patients by Solexa deep sequencing [7]. By systemically aligning the detected sequences to the miRNAome of Arabidopsis thaliana and soybean (Glycine max), multiple plant miRNAs were identified but only with sparse counts (Supplementary information, Table S1), possibly due to the 2'-O-methylation on the 3'-terminal ribose in plant-derived miRNAs that causes reduced ligation efficiency of adaptor oligonucleotides [37].…”
Section: Plant Mir159 Can Be Detected In Human Sera and Tumor Tissuesmentioning
confidence: 99%
“…Supplementary information, Table S1 indicating the plant miRNA alignment result is derived from our previously published serum smRNA-seq data set that includes 42 female stage II-III BC patients participating in neoadjuvant chemotherapy clinical trials at City of Hope [7]. All serum samples were collected at diagnosis before any treatment.…”
Section: Clinical Specimensmentioning
confidence: 99%
See 1 more Smart Citation
“…With the rapid development of high‐throughput sequencing technologies, researchers have identified plenty of miRNAs associated with breast cancer. For example, higher levels of circulating miR‐122 specifically predicted metastatic recurrence in patients with stage II‐III breast cancer 37. Besides, miR‐155 was up‐regulated greater than twofold in breast cancer compared with normal adjacent tissue (NAT),38 while a decreased level of serum miR‐155 was found after surgery and 4 cycles of chemotherapy 39.…”
Section: Resultsmentioning
confidence: 99%